A brief review on colon-specific drug delivery system for targeting to colonic region - Ghosh, Soumyadip; Majumdar, Subhabrota; Ganguly, Debgopal (Creative Pharma Assent, 2021)
Drug delivery to the colonic region refers to the drug that should have to released in the colonic environment instead of released in the upper gastrointestinal tract. To reach the site-specificity of the local treatment of the colon such as amoebiasis, colorectal cancer, and inflammatory bowel disease the target-specific drug delivery played an important role. To the establishment of the target-specific drug delivery to the colon, the various approach that has been explored include pH-dependent polymer, time-dependent, and bacteria-dependent drug delivery approach. Nanotechnology has been gaining much more interest due to target specificity and enhancement of bioavailability and high loading capacity. In this review, oral nanoparticle formulation for colon targeting specifically inflammatory bowel disease and suitable drugs for useful treatment and future aspects of nanoparticle formulation with particular approaches to enhancement of drug stability in the gastric environment have been covered.